On (intellectual) property and other legal frameworks in the digital economy: An economic analysis of the law - Christian Rusche; Marc Scheufen (Institut der deutschen Wirtschaft (IW), 2018)
The significance of data as an economic good in the digital economy quickly raises the question of who owns the data. More specifically, within the context of a data marketplace in which data is being exchanged or traded and where different bundles of rights (property rights) are trans-ferred (contract law) - an answer regarding the genuine assignment of property rights for data seems important. From an economic standpoint, this paper investigates the need for an (new) intellectual prop-erty right for data. Firstly, an overview of the status quo of the literature on property rights for data will be provided. This will be followed by an analysis of the characteristics of data as a good, clarifying the circumstances under which a market failure can occur. Accordingly, only a market failure situation will authorise economic policy intervention. Lastly, we will derive specific policy implications, offering economic reasoning on a new intellectual property right for data and spe-cifically pointing to other forms of law that may be more applicable for reaching an efficient allocation of data resources.
Keywords: D23; K11; K12; 330